2021
DOI: 10.1186/s42862-021-00012-0
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ use of ICT in implementing the competency-based curriculum in Kenyan public primary schools

Abstract: The use of Information and Communication Technology (ICT) in education has been widely advocated as much needed 21st-century skills by governments and policymakers. Nevertheless, several challenges in integrating ICT into the curriculum have been reported in previous research, especially in studies on Sub-Saharan African countries. Focusing on the case of Kenyan public primary schools, this study investigated the availability of ICT facilities; teacher capacity to integrate technology into their lessons; and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This was undoubtedly a positive thing to encourage the increase of ICT competence for ECTs (Sonia et al, 2019). More training, consultations, and workshops are needed to improve ICT competencies for the success of online learning (Abuhmaid, 2011;Purnomo & Ghofar, 2018;Wong & Daud, 2018;Murithi & Yoo, 2021). This suggests that the results align with the literature (e.g.…”
Section: The Significance Of Ict Competencies For Teachersmentioning
confidence: 67%
“…This was undoubtedly a positive thing to encourage the increase of ICT competence for ECTs (Sonia et al, 2019). More training, consultations, and workshops are needed to improve ICT competencies for the success of online learning (Abuhmaid, 2011;Purnomo & Ghofar, 2018;Wong & Daud, 2018;Murithi & Yoo, 2021). This suggests that the results align with the literature (e.g.…”
Section: The Significance Of Ict Competencies For Teachersmentioning
confidence: 67%
“…The study recommended the need for regular in-service training programme for teachers with a direct focus on ICT integration and ICT usage for teaching and learning. Murithi & Yoo (2021), in a study carried out among teachers in Kenyan public schools found that most of the teachers received only basic computer literacy training. It was also found that although teachers perceived the use of computers as necessary, they faced difficulties integrating technology in their lessons.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, Murithi and Yoo (2021) argue that, even though many educators have undergone training in incorporating ICT into their teaching methods, there remains a necessity for ongoing professional development since a significant portion of them continue to struggle with ICT integration in their teaching practices. What is of concern is when teachers view ICT as a "thing" for the younger generation teachers.…”
Section: Lack Of Skillsmentioning
confidence: 99%